From Highlands to Rainforests - Alelegn Wenedem Agegnehu; Tapimali Mafoligang Diane (African Journal on Land Policy and Geospatial Sciences)
ABSTRACT: Context and background: Beyond emissions reduction, safeguarding our land is a crucial front in the battle against climate change. Greenhouse gas emissions continue to rise, fueled by unsustainable energy use, land-use changes, and unsustainable consumption and production patterns worldwide, exposing vulnerable people in Cameroon and Ethiopia to severe damages. Their economies and livelihoods are highly vulnerable to the impacts of climate change due to the high dependence on rainfed agriculture and natural resources, as well as their relatively low adaptive capacity. Goal and Objectives: Observe climate events in both countries are projected to exacerbate under future climate change scenarios without immediate intervention. In this plan, land plays a dual role, serving as both a source and a sink for greenhouse gases. Sustainable land management can help mitigate the adverse effects of these multiple stressors on ecosystems and societies. Methodology: This paper employs both doctrinal and comparative research methods to examine how Ethiopia and Cameroon are using land policies to combat climate change. The doctrinal research method focuses on analyzing legal texts, policies, and frameworks related to land use and climate change. It examines legal principles, rules, and doctrines to understand the legal rationale behind land management strategies adopted in response to climate change. This paper also uses comparative research to identify similarities and differences in land policies between Ethiopia and Cameroon. The comparative analysis highlights the influence of historical, cultural, and environmental factors on land policies and examines the effectiveness of specific policy measures in mitigating climate change impacts. Results: It is obvious that human land use can affect the climate, and conversely, the climate can affect land uses. This closely circular relationship of interdependence places land at the heart of policies and laws organizing the response to climate change. This paper through in-depth country level Land laws and policies assessments aims to analyze how can land policies in both countries be harnessed as powerful tools to combat the escalating threat of climate change.